Industrial training report: Foxboro (M) Sdn. Bhd. / Aufa Afiqah Ahmad Zaini - Ahmad Zaini, Aufa Afiqah (Universiti Teknologi MARA, Perlis, 2023)
This internship report is based on my internship period from 15th August 2022 until today that I have successfully completed in Progressive Impact Corrosion Sdn Bhd under Progressive Impact Technology Sdn Bhd and Yayasan Zaiyadal. Progressive Impact Corrosion Sdn Bhd is an engineering company that provide solutions for corrosion. For the first three month, I have been assigned to work for two company which is PICORR and the other one is Foxboro (M) Sdn Bhd to the department of finance. I successfully accomplish all of my task given by my supervisor. Plus, I have also assisted in organizing their event as usherer for the Zaiyadal Group of Companies 2022 Finance & Governance Conference.The success of Progressive Impact Corrosion is determined by their SWOT and PESTEL analysis which is the strengths, they use shared service systems to achieve cost efficiency, their relationship between department manager and their subordinates are well cherished and appreciated and most important part is they have extensive 10 years of experiences in the field. Although they are lacks of worker, low cooperation from other department in process payment AP and pressures from unbalance workloads. They still got some improvements and opportunities to uphold which is they may be able to expand their business in foreign markets by partnering with regional businesses and the company could adapted to technological advancement through the years of operations. Lastly, they need to be aware of the threats they are facing such as competitors catching up with the product development and a changing political environment that could affect their business. In this report, I have discussed and gives some recommendations based on the company SWOT and PESTEL analysis.